2009
DOI: 10.1016/j.trstmh.2009.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Cost comparison of rapid questionnaire screening for individuals at risk of clonorchiasis in low- and high-prevalence communities in northern Vietnam

Abstract: SummaryClonorchiasis is an emerging food-borne trematode infection in Vietnam. Due to the absence of cost-effective preventive measures its control largely relies on morbidity reduction by chemotherapy with praziquantel. We performed a comparative cost estimation of three different diagnostic and intervention approaches in areas of high and low prevalence of clonorchiasis in northern Vietnam in order to select more cost-effective chemotherapy. Our study confirmed that a questionnaire investigating the habit of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…An obvious means of reducing infection would be to change such dietary habits; however, the habit of raw freshwater fish consumption is not going to be changed in a short period of time [ 7 , 20 ]. Accordingly, in community health surveys, we need to consider using the habit of raw freshwater fish consumption as a screening tool to select high-risk areas or individuals susceptible to C. sinensis infection [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…An obvious means of reducing infection would be to change such dietary habits; however, the habit of raw freshwater fish consumption is not going to be changed in a short period of time [ 7 , 20 ]. Accordingly, in community health surveys, we need to consider using the habit of raw freshwater fish consumption as a screening tool to select high-risk areas or individuals susceptible to C. sinensis infection [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the compliance in our study was excellent, but compliance may become a problem especially if preventive chemotherapy is continued for several years and without direct observed therapy [31] . Vietnam has also found it cost-effective to perform preventive chemotherapy as selective chemotherapy by only treating those who confirm that they have ever eaten raw fish [32] , [33] . However, Phan et al [27] found in a study involving 180 persons that 38.5% of those confirming eating raw fish were egg positive on microscopy, but also 25.8% of those who denied eating raw fish.…”
Section: Discussionmentioning
confidence: 99%
“…Main topics covered by the questionnaire were identical to the topics discussed in the groups. The use of questionnaires to investigate the habit of eating raw freshwater fish has previously been found to be a rapid, cost-effective, and operationally feasible tool for the identification of individuals at risk for FZT (Yajima et al, 2009).…”
Section: Study Sites and Selection Of Householdsmentioning
confidence: 99%